1991
DOI: 10.1111/j.1471-0528.1991.tb13514.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic problems in obstetrics and gynaecology in patients with congenital coagulopathies

Abstract: Objective-To review the obstetric and gynaecological problems in women with congenital coagulopathics. Design-Retrospective rcview.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 26 publications
2
135
0
1
Order By: Relevance
“…A report from Sweden showed that 9/136 women with VWD (6.8%) experienced hemorrhagic ovarian cysts [27]. There have also been reports of bleeding into the broad ligament with the patient presenting with a positive iliopsoas sign [28].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A report from Sweden showed that 9/136 women with VWD (6.8%) experienced hemorrhagic ovarian cysts [27]. There have also been reports of bleeding into the broad ligament with the patient presenting with a positive iliopsoas sign [28].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…This meets or exceeds the criteria for primary PPH [1]. Also, there appears to be a higher rate in type 2 (three patients) compared to type 1 patients [1, 23,28]. This may result in the need for red cell transfusions in between 7% [1] and 17% [5] of type 1 patients.…”
Section: Obstetric Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets contain 10%–15% of total blood vWF, and platelet transfusions have been used successfully to treat bleeding in patients with vWD 48. Platelet transfusion should be considered in patients with type 3 or platelet-low vWD to control bleeding that is not responsive or poorly responsive to replacement therapy with vWF concentrate.…”
Section: Adjunctive Treatmentsmentioning
confidence: 99%
“…Zu einem ähnlichen Ergebnis kamen Greer et al [13] in ihrer Studie. Der Erfolg der Therapie mit oralen Kontrazeptiva kann durch einen Anstieg der F VIII C-und vWF-Spiegel gezeigt werden [6].…”
Section: Von Willebrand-jürgens-syndromunclassified